Passenger lymphocyte syndrome due to anti‐B and anti‐Jka following combined intestinal and renal transplantation. (3rd June 2018) - Chua, C. C.; Lim, H.; Testro, A.; Hong, F. S.
Abstract : Introduction: Passenger lymphocyte syndrome (PLS) is an immune‐mediated haemolysis in which antibodies directed against recipient red‐blood‐cell (RBC) antigens are formed by viable donor B‐lymphocytes found within an allograft, leading to alloimmune destruction of recipient RBC. To our knowledge, this is the first reported case of PLS with anti‐B and anti‐Jk a after combined interstitial and renal transplants at the Australian Intestinal Transplant Service. Methods: A 47‐year‐old group B, RhD positive, Jk(a+b+) male received an ABO minor‐mismatch combined intestinal and renal transplants from a cadaveric donor who was group O RhD positive. The recipient developed clinically significant haemolysis 18 days post‐transplant with a haemoglobin nadir of 59 g/l. He was supported with donor and recipient compatible blood components, with laboratory evidence of resolution of haemolysis by day 52 post‐transplant without requiring any additional interventions. Results: Both the recipient and donor had a negative antibody screen immediately prior to transplantation. Two alloantibodies, anti‐B and a weak anti‐Jk a, were detected in the recipient's eluate. Discussion: It is important to be vigilant about possible PLS post‐transplant especially in high‐risk populations such as those undergoing intestinal and/or multi‐visceral transplant with minor ABO‐incompatible allografts. Although PLS is a rare and self‐limiting condition, early recognition allows timely provision of compatible blood components as well as minimisation of morbidity from haemolysis.